The opening of the rule in triadic games and the paradox in connectivity deficit (Agora for Physical Education and Sport, 2021)
The opening of the rule favors the appearance of paradoxes during the triadic game, taking advantage of the permitted communication. It was analyzed, in the same team chasing game, the effect on the gameplay of connectivity scarcity ('structural hole') in two triad structures (complete and non-complete), to compare: the interactions derived from the network of motor communication, the directed flows and the emissions and receptions framed in the intragroup and intergroup values, taking the roles as added tags to the flow, and the utility value of strategic decisions. The connectivity deficit of the non-complete triad is filled by solving ambivalent situations for the benefit of their teams strategies, aided by an ‘instrumental meta-communication’ that contributes to the progress of the scoring or results system. This effect reduces complexity and has positive consequences on gameplay.
Keywords: triad; complexity; games; physical education